Sinergi Paramassa: Implementation of the Social Values of the Meugang Tradition into Digital Music Composition - Rico Gusmanto; Berlian Denada (Universitas Negeri Medan, 2023)
The Meugang tradition as Acehnese local wisdom is an activity that has a togetherness. This togetherness is a social value that creates a harmonious society in the midst of the globalization era. This is something interesting to implement in the form of music compositions. The aim of this research is to create a music that implement social values in the Meugang tradition through the use of a Digital Audio Workstation. The method used is an artistic research method which consists of 1) the formulation of ideas; 2) determine the work; 3) express ideas; 4) and performances. The result of this research is music entitled